(untitled) (Eurasian Research Bulletin, 2024)
In this article, tax systems mainly rely on accurate and up-to-date information about taxpayers and tax objects. Such a data storage mechanism forms the basis of effective tax administration, revenue collection, compliance monitoring and policy implementation. This article provides a comprehensive overview of the mechanisms used by governments to manage taxpayer information and track taxable entities. Based on examples from different jurisdictions, it explores the key components, functions, challenges and best practices associated with these mechanisms.